2008
DOI: 10.1002/cncr.23658
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive effects of hormone therapy in men with prostate cancer

Abstract: BACKGROUND Men who receive androgen-deprivation therapy (ADT) for prostate cancer experience several side effects from this treatment. A few recent studies have examined the cognitive implications of ADT and how they impact a patient’s treatment decision-making, occupational pursuits, and quality of life. For this report, the authors explored possible mechanisms for this association, reviewed research in animal studies and aging men, and examined the growing literature focused on the relation between ADT and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
182
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(189 citation statements)
references
References 56 publications
4
182
0
3
Order By: Relevance
“…Section summary. Overall, consistent with findings from a previous review, 12 these three rather small studies indicate an appreciably reliable finding of impaired spatial memory and spatial abilities in men receiving ADT for prostate cancer compared to healthy controls. These deficits appeared during the third month of treatment with ADT but were not found again at 9 months regardless of whether the patient was still receiving ADT.…”
Section: Adt and Cognitionsupporting
confidence: 90%
See 1 more Smart Citation
“…Section summary. Overall, consistent with findings from a previous review, 12 these three rather small studies indicate an appreciably reliable finding of impaired spatial memory and spatial abilities in men receiving ADT for prostate cancer compared to healthy controls. These deficits appeared during the third month of treatment with ADT but were not found again at 9 months regardless of whether the patient was still receiving ADT.…”
Section: Adt and Cognitionsupporting
confidence: 90%
“…11 A thorough review of the clinical literature was published in 2008 and indicated that although studies suffered from small sample sizes, there was a strong argument that ADT is linked to subtle but significant cognitive declines in men with prostate cancer. 12 Since that publication, new high-quality evidence has emerged, 13 warranting a reexamination of the data.…”
Section: According To the World Health Organization (Who) Internationalmentioning
confidence: 99%
“…73 Although there appear to be specific mechanisms for testosterone to directly impact cognition, it is possible that the side effects of androgen ablation therapy (e.g., hot flashes, fatigue and anaemia) may contribute indirectly to impaired cognition. Clearly, some findings have been inconsistent because of low sample size and inadequate controls.…”
Section: Cognitive and Affective Symptomsmentioning
confidence: 99%
“…73,75 Fatigue, sleep disturbance and depression PCa patients commonly state that fatigue, insomnia and depression are the most troublesome side effects of ADT. 76 Hot flashes have been specifically linked to insomnia and disrupted sleep patterns and have been shown to contribute to depression in the elderly patients on ADT.…”
Section: Cognitive and Affective Symptomsmentioning
confidence: 99%
“…Several prior studies had shown declines due to ADT in executive functions and visuospatial abilities; however, previous studies have been inconsistent in their findings often suffering from low sample size and inadequate controls. 6 The effect of therapy on cognitive function has been a pertinent topic recently, with terms like 'chemo fog' and 'chemo brain' now routinely used to describe the cognitive effects of systemic chemotherapy. In their report, the authors presented a prospective matched cohort study to more conclusively answer this question.…”
mentioning
confidence: 99%